1987
DOI: 10.1523/jneurosci.07-03-00733.1987
|View full text |Cite
|
Sign up to set email alerts
|

Voltage clamp analysis of cholinergic action in the hippocampus

Abstract: A slow muscarinic EPSP, accompanied by an increase in membrane input resistance, can be elicited in hippocampal CA1 pyramidal cells in vitro by electrical stimulation of cholinergic afferents in the slice preparation. Associated with the slow EPSP is a blockade of calcium-activated potassium afterhyperpolarizations (AHPs) (Cole and Nicoll, 1984a). In this study a single-electrode voltage clamp was used to examine the currents affected by activation of muscarinic receptors, using either bath application of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
327
2
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(364 citation statements)
references
References 23 publications
32
327
2
3
Order By: Relevance
“…For example, cholinergic stimulation caused depolarization due to a decrease in the K¤ leakage conductance in the hippocampus (Madison et al 1987;Benson et al 1988). In neurones dissociated from rat neostriatum, histamine reduced the K¤ leakage currents by activation of both H1 and Hµ receptors (Munakata & Akaike, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cholinergic stimulation caused depolarization due to a decrease in the K¤ leakage conductance in the hippocampus (Madison et al 1987;Benson et al 1988). In neurones dissociated from rat neostriatum, histamine reduced the K¤ leakage currents by activation of both H1 and Hµ receptors (Munakata & Akaike, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Besides depolarization by blocking potassium conductances [70,71] and disinhibition by suppressing GABA release [72], acetylcholine in the hippocampus may potentiate basal-dendritic LTP by facilitating NMDA receptors and their signaling pathways [73,74]. LTP in hippocampal CA1 is sensitive to NMDA receptor antagonists including open-channel blocker MK-801 [75,76].…”
Section: Vestibular Stimulation Enhances Ltpmentioning
confidence: 99%
“…The effect of cholinergic neuromodulation was modeled by altering the conductance (g leak , from 2×10 −5 to 1.8× 10 −5 S cm −2 ) and reversal potential (E leak , from −60 to −58 mV) of the leak current and the conductance of I KM and I KAHP . Madison et al (1987) showed that in hippocampal pyramidal neurons, these two currents are both cholinergically modulated, albeit with different sensitivities. I KAHP is inhibited by cholinergic modulation at about ten times lower concentrations than I KM (IC 50 =0.3 and 5 μM for carbachol).…”
Section: Simple Single-compartment Neuronmentioning
confidence: 99%
“…Cholinergic modulation affects a variety of both ionotropic (nicotinic) and metabotropic (muscarinic) receptor targets (Schoebesberger et al 2000). Acetylcholine acting on muscarinic receptors downregulates several slow potassium currents (I KM , I KAHP (Madison et al 1987;McCormick 1993)), and changes the input resistance by down regulating the leak conductance. These currents control cellular excitability and repetitive firing of cortical pyramidal neurons.…”
Section: Introductionmentioning
confidence: 99%